ANALISIS BEBAN KERJA DAN POSTUR KERJA PADA PEKERJA BENZ AIRBRUSH DENGAN PENDEKATAN RAPID ENTIRE BODY ASSESSMENT (REBA) UNTUK MENGURANGI RISIKO MUSCULOSKELETAL DISORDERS (MSDS) - Rere Danang Adhitya, - (2019)
Work with a lack of tools and less ergonomic work posture results in musculoskeletal disorders. This problem was found in the small airbrush helmet industry at work stations washing helmets, helmet sanding, helmet motif formation and painting motives for helmets. So in this study provide a solution in the form of appropriate tools to reduce the risk of musculoskeletal disorders. The study began by giving Nordic Body Map questionnaires to workers to find out complaints that occurred to workers at work. Then calculate the pulse of the workers and observe the workers by taking photos to be tested for large REBA values. The final results of REBA show that the work posture with the proposed design of tools to be more ergonomic